Typography of Croatian birth certificates, certificates of nationality and grade report cards from the early 20th century (Libellarium: journal for research in the field of information and related sciences, 2011)
The paper investigates the typographic elements in birth certificates, certificates of nationality and report cards printed in Croatia in the early 20th century, with the aim of making a chronological overview. The availability of visual and instrumental devices for expert analyses made this kind of analysis of Croatian historical documents possible. The research was conducted using non-evasive forensic methods, and it is based on the printing techniques and methods of reproducing particular typographic elements.The archival material analyzed in this study dates back to the early 20th century and originates from private sources. The only exception is a report card from 1855, stored in the archives of the School Museum, which was used to illustrate typographic differences at the turn of the century.The analysis of the script, language, format, font and illustrations gave insight into the changes of typography over time. It all defines the symbolism of documents, which reflect national and religions connotations. This confirms the basic presupposition that the change of typographic elements is brought about as a result of two parameters: technological development and national changes.
Keywords: typography; history; birth certificate; certificate of nationality; grade report cards; font; print